One third octave analysis: a diagnostic tool to measure nasality in conjunction with nasalance in children with repaired cleft lip and palate - A, Navya; M, Pushpavathi (Journal of All India Institute of Speech and Hearing, 2013)
Hypernasality is the most predominant feature perceived in speech of individuals with cleft lip and palate. Instrumental assessment of speech can provide additional information along with the perceptual evaluation of speech for accuracy in diagnosis in individuals with cleft lip and palate (CLP). The widely used objective assessment of nasality is measuring nasalance using Nasometer. However, the spectral analysis of nasality in speech can provide complementary information along with nasalance measures. Hence, the present study is aimed to measure nasalance values and one third octave spectral peaks and their ability to differentiate children with repaired cleft lip and palate (RCLP) from control group. The study included eight children with RCLP age ranging from six to ten years. The control group included sixteen typically developing age and gender matched children. Vowel /a/ and /i/ was selected as stimuli. Nasalance was measured using Nasometer and 1/3rd octave spectral analysis was measured using a specially designed MATLAB programme. Statistical analysis was performed using SPSS 17 software. To differentiate the groups with the cutoff values, sensitivity and specificity of the variables was derived using receiver operating curves (ROC). The results showed high sensitivity and specificity of the nasalance values with the cutoff of 8.8% for /a/ and 31.6% for /i/. The frequency region between 998Hz and 2663 Hz provided high sensitivity and specificity for differentiating groups using 1/3rd octave spectra analysis. Further studies are required to generalize the results of one third octave spectra analysis.